For whom the text speaks? The enunciatee’s image in the Neverending story - Matte, Ana Cristina Fricke (Laboratório Editorial FCL-UNESP, 2008)
The movie Neverending story, object of this paper, links together two different stories, each one with its own subject (that one from the movie and that one from the book read into the movie). The analysis shows a participant enunciatee: the third protagonist. In this work we present: (i) our proposal of approach for a subject and aspectuality based building of the enunciatee's image and (ii) a discussion of some theoretical-practical possibilities of such an approach.